2016
DOI: 10.1152/jn.00206.2016
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic adaptation to a systematically varying disturbance

Abstract: Saccadic adaptation maintains the correct mapping between eye movements and their targets, yet the dynamics of saccadic gain changes in the presence of systematically varying disturbances has not been extensively studied. Here we assessed changes in the gain of saccade amplitudes induced by continuous and periodic postsaccadic visual feedback. Observers made saccades following a sequence of target steps either along the horizontal meridian (Two-way adaptation) or with unconstrained saccade directions (Global a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 84 publications
1
26
0
Order By: Relevance
“…In this paradigm, the trans-saccadic size change followed a time-varying, sinusoidal evolution as a function of trial number. In a first experiment, we observed that a sinusoidal evolution of trans-saccadic size change produced a sinusoidal evolution of adjusted size, with a time course closely resembling the one that Cassanello, Ohl and Rolfs (2016) obtained in saccade adaptation. This result indicates that peripheral size recalibration and saccadic adaptation have comparable temporal dynamics when driven by stimuli modulated in a similar way.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…In this paradigm, the trans-saccadic size change followed a time-varying, sinusoidal evolution as a function of trial number. In a first experiment, we observed that a sinusoidal evolution of trans-saccadic size change produced a sinusoidal evolution of adjusted size, with a time course closely resembling the one that Cassanello, Ohl and Rolfs (2016) obtained in saccade adaptation. This result indicates that peripheral size recalibration and saccadic adaptation have comparable temporal dynamics when driven by stimuli modulated in a similar way.…”
Section: Introductionsupporting
confidence: 62%
“…Note, however, that because participants must adjust the size of the stimuli, the trials last much longer (around five trials per minute) than trials in saccade adaptation (up to 100 trials per minute), meaning that if the frequency was defined in terms of cycles per minute, all frequencies in the saccade adaptation study would be much higher than in the current study. With these caveats in mind, the condition in the study by Cassanello et al (2016) that is most comparable to our study (i.e., two-way saccadic adaptation with 100 trials per cycle) produced oscillations in the saccadic gain that had average amplitude of 12% relative to the amplitude of the modulation of the trans-saccadic step. The average lag was 10.49 trials.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Additionally, comparing the remembered location of visual objects before a saccade to their location after may also be used to estimate how far the eyes previously moved. Indeed, if the saccade target remains visible after the movement, the accuracy of the saccade can be inferred from the proximity of the target to the fovea (Cassanello et al, 2016;Collins and Wallman, 2012). This influence is most apparent when -rather than remaining stationary throughout the movement -the saccade target is covertly displaced mid saccade.…”
Section: Introductionmentioning
confidence: 99%